38 The outcomes of patients post cardiac arrest in the primary PCI era: the ST James experience. (28th September 2016) - O'Connor, C; Murphy, R; O'Hare, D; Yearoo, I; Cuddy, S; Ullah, I; McGuane, D; Sullivan, V; Foley, B; Mellotte, G
Abstract : Introduction: Ischaemic heart disease is believed to account for 60–70% of cardiac arrests, particularly in adults. Since the commencement of the national primary PCI programme, there is increased access to angiography in patients with return of spontaneous circulation (ROSC) post cardiac arrest. The decision to proceed with angiography can be challenging in this cohort as it is often difficult to determine candidates suitable for primary angiography for several reasons; non-specific electrical morphology on electrocardiogram post-arrest, sluggish myocardial contractility often seen in patients on echocardiography after ROSC, the difficulty in determining the degree of hypoxic encephalopathy in the acute setting and the challenge in identifying the aetiology for the cardiac arrest initially. This study aimed to identify the patients presenting to the emergency department with out of hospital cardiac arrest over a two year period, and describe associated outcomes in the 'primary PCI' era. Methods: Retrospective cohort analysis was conducted on attendances to the emergency department of St James hospital, Dublin between January 2014 and February 2016. Emergency department records were collated with hospital inpatient enquiry (HIPE) records to identify patients presenting with cardiac arrest. Electronic and paper charts were used to source patient-level data. Standard parametric multivariate analysis was performed. Results: Over the 109, 854 emergency department attendances during the study period, 290 patients presented with cardiac arrest (0.26%). Average age on presentation with cardiac arrest was 65, and the male-female ratio was observed at 2:1. 52 patients (17.9%) survived to admission from the emergency department. Of the patients surviving arrest, 23 (44.2%) underwent emergency angiography; 52.2% within 90 minutes, 78% within 6 hours and 82.6% within 24 hours. 15 (65.2%) patients required primary PCI. 60.9% of patients undergoing angiography survived to discharge, whereas 24% of the group not undergoing angiography survived to discharge. This is a reflection on angiography not being performed on patients with poor expected outcomes. There was a trend towards increased survival in the patients not requiring PCI which was not significant (53.3% versus 71.4%, p = 0.14), and this again reflects the increased comorbidity burden of those requiring PCI. Compared with STEMI patients within the same St James Hospital population (mean reperfusion time 116 mins) patients requiring reperfusion had a significantly longer time to reperfusion (263 mins) p = 0.0022. Conclusion: Out of hospital cardiac arrest was associated with a total mortality of 91% in this cohort. In carefully selected patients post cardiac arrest, a high percentage (65.2%) required PCI. Patients with out of hospital cardiac arrest requiring revascularisation had a longer time to reperfusion than STEMI patients.